2008
DOI: 10.1111/j.1600-079x.2008.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces stress‐activated/mitogen‐activated protein kinases in spinal cord injury

Abstract: Permanent functional deficits following spinal cord injury (SCI) arise from both mechanical injury and from secondary tissue reactions involving inflammation. The mitogen-activated protein kinases (MAPKs) play a critical role in cell signaling and gene expression. MAPK family includes three major members: extracellular signal regulated kinase (ERK), p38, and c-Jun N-terminal kinase (JNK), representing three different signaling cascades. Moreover, various studies have clearly shown that high-mobility group box … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 60 publications
(76 reference statements)
4
35
0
Order By: Relevance
“…Moreover, melatonin’s protective role in SCI was related to the regulation of MAPK signaling pathways and the high-mobility group box 1 protein expression (HMGB1) in mice. Melatonin treatment in SCI mice enhanced motor recovery, reduced the activation of p38 MAPK, JNK, and ERK1/2, and the expression of HMGB1 [50]. An earlier report also showed that activation of the endogenous melatonin system in the spinal cord reduced the generation, development, and maintenance of central sensitization, with a resultant inhibition of capsaicin-induced secondary mechanical allodynia and hyperalgesia [204].…”
Section: Effect Of Melatonin On Traumatic Cns Injuriesmentioning
confidence: 97%
“…Moreover, melatonin’s protective role in SCI was related to the regulation of MAPK signaling pathways and the high-mobility group box 1 protein expression (HMGB1) in mice. Melatonin treatment in SCI mice enhanced motor recovery, reduced the activation of p38 MAPK, JNK, and ERK1/2, and the expression of HMGB1 [50]. An earlier report also showed that activation of the endogenous melatonin system in the spinal cord reduced the generation, development, and maintenance of central sensitization, with a resultant inhibition of capsaicin-induced secondary mechanical allodynia and hyperalgesia [204].…”
Section: Effect Of Melatonin On Traumatic Cns Injuriesmentioning
confidence: 97%
“…In previous studies, SCI has been effectively treated with 50 or 100 mg/kg melatonin [25][26][27] . Gül et al reported the neuroprotective effects of melatonin on experimental SCI in rats 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HMGB1 has been shown to be elevated in both the spinal cord tissue and the serum of rodents with spinal cord ischemic injury (53,54). Moreover, melatonin, ethyl pyruvate and hydrogen gas were found to reduce motor neuron apoptosis, improve motor dysfunction and attenuate the release of HMGB1 in rodents with SCI (51,53,54). Previous studies have implicated that HMGB1 directly induces apoptosis in neural cells (32,33), aggravates infarction volume and exacerbates the neurological deficit in transient cerebral ischemia in rats (36,55).…”
Section: Hmgb1 In Spinal Cord Injurymentioning
confidence: 99%
“…Recently, HMGB1 has been shown to be elevated in the spinal cord tissue of rodents with spinal cord compression injury and is associated with neuronal cell apoptosis (51,52). Furthermore, HMGB1 has been shown to be elevated in both the spinal cord tissue and the serum of rodents with spinal cord ischemic injury (53,54).…”
Section: Hmgb1 In Spinal Cord Injurymentioning
confidence: 99%